Effects of an online self-assessment tool on teachers' digital competencies - Abbiati, Giovanni,Azzolini, Davide,Balanskat, Anja,Engelhart, Katja,Piazzalunga, Daniela,Rettore, Enrico,Wastiau, Patricia (IZA - Institute of Labor Economics, 2023)
We evaluate the effects of an online self-assessment tool on teachers' competencies and beliefs about ICT in education. The causal impact of the tool is evaluated through a randomized encouragement design, involving 7,391 lower secondary teachers across 11 European countries. Short-run impact estimates show that the use of the tool led teachers to critically revise their technology-enhanced teaching competencies (-0.14 standard deviations) and their beliefs about ICT in education (-0.35 s.d.), while there is no impact on their probability of taking specific training. The effects are concentrated among teachers in the top-end tail of the distribution of pre-treatment outcomes. We provide suggestive evidence that the feedback score provided by the tool triggered such results by providing a negative information shock.
10419/272490
Keywords: Graue Literatur; ICT; technology-enhanced teaching; self-assessed competencies; experimental design; teaching practices